Analisis Kepuasan Konsumen dalam Memediasi Pengaruh Citra Merek dan Kualitas Produk terhadap Minat Beli Konsumen - Putra, Putu Eka Prayoga; Suartina, I Wayan; Pratiwi, Komang Ary (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Generating purchase interest is critical to the survival of your company. This will sell all the products sold in the future and increase sales. The purpose of this study was to determine the impact of brand image and product quality on purchase intention through consumer satisfaction as a mediating variable. The study population is all consumers of the Winata Ikat Weaving Company, with a total sample of 90 respondents identified using targeted sampling methods. Data were collected through observations, interviews, documentation, literature searches, and questionnaires. The data analysis technique used in this study is the path analysis technique. Based on the research results, we can say: Brand image has a significant positive impact on consumer purchase intentions. Product quality has a significant positive impact on consumer purchase intentions. Consumer satisfaction conveys the impact of a brand's image on purchase intent. Consumer satisfaction conveys the impact of product quality on purchase intention. In light of the research, Tenun Ikat Winata must continue to innovate to create appealing product designs for consumers that are different from their competitors in order to increase consumer interest.